Comparing suturing techniques and materials in hypospadias repair: a prospective cohort study - Nainggolan, Ebram; Raharja, Putu Angga Risky; Situmorang, Gerhard Reinaldi; Rodjani, Arry; Wahyudi, Irfan (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Various techniques are available for hypospadias surgery, but the most effective suturing techniques and suture materials remain debated. This study aimed to evaluate the outcomes of hypospadias repair using various suturing techniques and materials. METHODS This prospective cohort study was conducted from August 2023 to August 2024 and included all patients who underwent hypospadias surgery at Cipto Mangunkusumo Hospital. We compared the outcomes of 2 suturing techniques (interrupted versus continuous) and 2 suture materials (6-0 polydioxanone [PDS] versus poliglecaprone 25) used for neourethra suturing. Follow-up assessments were conducted at 1, 2, and 4 weeks postoperatively, and subsequently every 3 to 6 months, focusing on complications. RESULTS 162 participants were included, with a mean age of 6.27 (3.99) years and a mean follow-up period of 20.39 (14.25) weeks. Complications occurred in 31 patients (19.1%), with a significant association between hypospadias type and complication occurrence (p = 0.039). Complication rates were 9.4% in distal, 12.5% in midshaft, and 26.8% in proximal cases. No significant differences were found between suturing techniques (interrupted: 19% versus continuous: 12%, p = 0.429) or suture materials (6-0 PDS: 22% versus 6-0 poliglecaprone 25: 9%, p = 0.998). Subgroup analyses by hypospadias type also showed no significant differences by suture type or technique (all p>0.05), although a trend toward significance was noted in proximal cases (p = 0.062). CONCLUSIONS The choice of suturing techniques and suture materials does not affect complication rates in hypospadias repair, allowing surgeons to decide based on personal expertise and preference.